Nancy Clancy, late-breaking news! - O'Connor, Jane (O'Connor, Jane. Nancy Clancy, 2017)
When she decides that the articles in the latest issue of the Third Grade Gazette are not interesting enough, Nancy sets out to find some news worth reporting on.